Tuning of the electronic structure and magnetic properties of xenon ion implanted zinc oxide. (13th February 2018) - Ghosh, B; Ray, Sekhar C; Pattanaik, Shreenu; Sarma, Sweety; Mishra, Dilip K; Pontsho, Mbule; Pong, W F
Abstract: A correlation between the electronic structure and magnetic properties of ZnO single crystals (ZnO SCs) and 300 keV xenon ion (Xe 3+ ) implanted ZnO SCs has been studied using x-ray absorption near edge structure (XANES) spectroscopy, valence band photoemission spectroscopy (VB-PES), x-ray photoelectron spectroscopy, ultraviolet photoelectron spectroscopy, and a superconducting quantum interference device-type magnetometer. The XANES studies revealed that the number of unoccupied p -states in the implanted ZnO SCs is higher than in the pristine ZnO SCs. In the implanted ZnO SCs, the binding energy of the Zn 2 p 3/2 core level peak shifted to higher energy which further confirmed the increase in the valence band maximum (VBM) energy level. The VBM of the xenon ion (Xe 3+ ) implanted ZnO SCs increased from 3.17–3.49 eV, obtained from UPS (He-I) measurements. A VB-PES study revealed that the number of electrons in the valence band of the O 2 p –Zn 4 sp hybridized states of the implanted ZnO SCs is higher than in the pristine ZnO SCs. The magnetic M – H loops demonstrated enhanced room temperature ferromagnetism in the Xe implanted ZnO SCs, attributable to the increasing number of surface defects and native defect sites in oxygen vacancies and zinc interstitials.